Shear wave elastography for extracranial carotid atherosclerotic plaques: technical principles and how to do it - Mellucci Filho, Pedro Luciano [UNESP]; Bertanha, Matheus [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Yoshida, Winston Bonetti [UNESP]; Sobreira, Marcone Lima [UNESP] (FapUNIFESP (SciELO), 2023)
In the wake of studies targeting atherosclerotic plaques and searching for quantifiable variables that contribute additional information to therapeutic decision-making, plaque assessment using Shear Wave Elastography (SWE) is emerging as a reproducible and promising alternative. We used a single Logiq S8 device (General Electric, Boston, Massachusetts, United States) with an 8.5-11MHz multifrequency linear transducer at 10MHz in longitudinal section. We considered relevant criteria for image acquisition: adequate longitudinal insonation, differentiation of the intima-media complex, delineation of proximal and distal tunica adventitia and the vascular lumen, good visualization of the atherosclerotic plaque, cardiac cycle in ventricular diastole, and absence of incongruous changes. SWE is an emerging and extremely promising method for assessment of carotid plaques that may contribute to therapeutic decision-making based on characteristics related to the atherosclerotic plaque, with inter-device and inter-examiner reproducibility.
Elastografia por cisalhamento (shear wave) para placas ateroscleróticas carotídeas extracranianas: princípios técnicos e como realizar
Keywords: carotid artery diseases; carotid stenosis; computer-assisted image interpretation; Doppler ultrasonography; elasticity imaging techniques